ANALYSIS OF CAUSES OF SIGNIFICANT INCREASE IN THE INDOSAT PROFIT IN 2019 - Rudi Triadi Yuliarto; Girang Permata Gusti (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2020)
This study aims to make in-depth observations of the company's financial statement records, to find out what strategies the company uses so that it can significantly increase product sales, and to examine which parts of the business units contribute the most to company profits. This research used descriptive method. This study uses quantitative data types, in the form of secondary data obtained from the company's annual financial statement documentation for 10 years (2010-2019) for the company's net income and 5 years (2015-2019) for operating income. Indosat's business strategy model that continues to invest in the discounting section deserves high appreciation. The company's serious effort to be able to provide quality products and services at affordable prices can finally provide optimal results. This can be seen from Indosat's data sales (internet package) which rose significantly in 2019 amounting to 15.37 trillion rupiahs, compared to 2018 which only amounted to 12.51 trillion rupiahs. The courage of the company to decide to continue to provide subsidized funds in the form of discounts for its customers when the company's finances are experiencing losses is very exemplary.